PERAN PROFITABILITAS DALAM MEMEDIASI HUBUNGAN ANTARA GREEN ACCOUNTING, ESG DAN NILAI PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN DI INDONESIA - Siregar, Inova Fitri; Rasyad, Rinayanti; Onasis, Dini; Hardi, Hardi (Jurnal Akuntansi Kompetif, 2025)
Firm value reflects the market's perception of the intrinsic value of the company, which includes growth potential, profitability, and environmental risk, which is rarely studied, especially in developing countries with environmental standards and regulations that have not yet become mandatory rules, such as Indonesia. This study aims to measure the effect of green accounting and ESG on firm value, including profitability as mediation. The method used is quantitative method with a sample of mining companies as much as 40 data collected. The results show that green accounting and ESG have a significant effect on firm value, while the role of profitability as mediation is only able to connect green accounting indirectly, this is because the implementation of environmental accounting practices can reduce the company's market value. In the context of stakeholder theory, although green accounting helps companies meet stakeholder demands related to environmental responsibility and increases transparency, the cost of implementation may be higher than the direct benefits seen in firm value in the short term.